Determinants of ICT Tools Accessibility by Farmers in Bihar - Shreya Anand; Satya Prakash, A.K Singh (Indian Journal of Extension Education, 2022)
The economy of a developing country like India is mostly dependent on the performance of the agriculture sector, and its growth highlights the need of transferring relevant timely information to farmers. Information and communication technology (ICT) plays an important role in this regard. India is progressively using ICT in its national development strategy and implementing tactics for widespread promotion in order to develop the country into a knowledge-rich, e-learning society. The study was conducted during the year 2019 to determine the degree of access and use of ICTs by farmers and its determinants covering a random sample of 100 farmers in Katihar and Samastipur districts of Bihar. The majority of farmers were young and educated up to high school, mostly accessed mobile phone among the ICT tools. Farmers’ diversified occupation, education, annual income, farming system/allied agricultural activities, mass media exposure, and extension contact were positively and significantly correlated with the accessibility of ICT tools. The regression model revealed that selected farmers’ attributes explained about 61 percent variation in the accessibility of ICT tools by the farmers.